2023
DOI: 10.1088/1748-9326/acf727
|View full text |Cite
|
Sign up to set email alerts
|

Tackling policy leakage and targeting hotspots could be key to addressing the ‘Wicked’ challenge of nutrient pollution from corn production in the U.S.

Jing Liu,
Laura Bowling,
Christopher Kucharik
et al.

Abstract: Reducing nutrient loss from agriculture to improve water quality requires a combination of management practices. However, it has been unclear what pattern of mitigation is likely to emerge from different policies, individually and combined, and what the consequences would be for local and national land use and farm returns. We address this research gap by constructing an integrated multi-scale framework for evaluating alternative nitrogen loss management policies for corn production in the US. This approach co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Papers in this special issue touch on all aspects of these criteria. For example, Liu et al (2023) found that wetland restoration was the most effective in reducing nitrate loss in the Mississippi Basin, but installing controlled drainage was the most efficient (i.e., nitrate loss per $ invested). Both Liu et al (2023) and Haqiqi et al (2023b) find that coupled strategies, that are often synergistic, are much more effective in achieving sustainability goals compared to single strategies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Papers in this special issue touch on all aspects of these criteria. For example, Liu et al (2023) found that wetland restoration was the most effective in reducing nitrate loss in the Mississippi Basin, but installing controlled drainage was the most efficient (i.e., nitrate loss per $ invested). Both Liu et al (2023) and Haqiqi et al (2023b) find that coupled strategies, that are often synergistic, are much more effective in achieving sustainability goals compared to single strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al (2023) found that wetland restoration was the most effective in reducing nitrate loss in the Mississippi Basin, but installing controlled drainage was the most efficient (i.e., nitrate loss per $ invested). Both Liu et al (2023) and Haqiqi et al (2023b) find that coupled strategies, that are often synergistic, are much more effective in achieving sustainability goals compared to single strategies. The study by Ray et al (2023) finds that, under a restricted labor mobility situation, regions targeted for the sustainable groundwater use policy will see sharp decrease in wages, but the spillover effects will increase wages in non-targeted regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations